2013
DOI: 10.4103/0970-1591.120123
|View full text |Cite
|
Sign up to set email alerts
|

Fetus in bladder

Abstract: This is the first reported case of vesicouterine fistula presenting with a fully formed dead fetus in the urinary bladder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…The first case of finding a fetus in the bladder was reported by Banale and coauthors [11]. A patient, who previously had had two Cesarean sections, presented with complaints of pain in the abdomen and macrohematuria.…”
Section: Discussionmentioning
confidence: 99%
“…The first case of finding a fetus in the bladder was reported by Banale and coauthors [11]. A patient, who previously had had two Cesarean sections, presented with complaints of pain in the abdomen and macrohematuria.…”
Section: Discussionmentioning
confidence: 99%
“…This appears to be the second case reported in the medical literature. Although there are some reports of umbilical cord prolapse through the urethra due to VUF, laparotomy findings of a fetus inside the bladder due to spontaneous rupture of the uterus after an attempt of labor induction or unsuccessful curettage, ( 4 ) only Sapre et al, attained to describe a case in which a dead fetus was found inside the urinary bladder after migration through a VUF. ( 5 )…”
Section: Discussionmentioning
confidence: 99%
“…Según diferentes autores, (Banale et al, 2013), (Birge et al, 2015), (Park et al, 1999) la existencia de piocolpos se produce debido a una infección del flujo vaginal, este es un cuadro muy poco frecuente y su incidencia se estima en un 0,1 a 0,05%. En el Hospital General Ambato desde el año 2010 hasta la actualidad solo se han presentado un total de 6 casos, lo que representa el 0,6 % de este padecimiento por año calendario.…”
Section: Introductionunclassified